High-performance, flexible thermoelectric generator based on bulk materials - Qian Xu; Biao Deng; Lenan Zhang; Shaoting Lin; Zhijia Han; Qing Zhou; Jun Li; Yongbin Zhu; Feng Jiang; Qikai Li; Pengxiang Zhang; Xinbo Zhang; et al. (Cell Reports Physical Science, 2022)
Summary: Flexible thermoelectric generators (f-TEGs) are promising solutions to power supply for wearable devices. However, the high fabrication costs and low output power density of conventional f-TEGs limit their applications. Here, we present a bulk-material-based f-TEG featuring multifunctional copper electrodes for heat concentration and dissipation and fabrics for comfort and heat-leakage reduction. When worn on the forehead, our f-TEG’s maximum output power density (based on the device’s area) reaches 48 μW/cm2 at a wind speed of 2 m/s and an ambient temperature of 15°C. A light-emitting diode (LED) powered by our f-TEG headband with 100 pairs of thermoelectric pillars can illuminate a paper for reading in a dark room at 17.5°C without an external heat sink or forced convection at the cold side. This work provides a general design approach for high-performance f-TEGs at a low cost. The device-level perspectives fill the critical knowledge gap between state-of-the-art material innovations and practical thermoelectric applications.